Stability and Variable Admittance Control in the Physical Interaction with a Mobile Robot. (8th December 2015) - Wang, Hongbo; Patota, Federico; Buondonno, Gabriele; Haendl, Markus; De Luca, Alessandro; Kosuge, Kazuhiro
Admittance controllers have been widely implemented in physical human/robot interaction (pHRI). The stability criteria and the parameter adaptation methods for admittance control have been well-studied. However, the established methods have mainly focused on human/manipulator interaction, and cannot be directly extended to mobile robot-based pHRI, in which the nonlinearity cannot be cancelled by feedback linearizations and the measurements of the relative human/robot position and orientation are usually lacking. In this paper, we study the pHRI between a human user and a mobile robot under admittance control. We develop a robotic system which can measure the relative chest/ankle positions of the human user with respect to the robot. Using the measured human position, a human frame admittance controller is proposed to remove the nonlinearity in the system dynamics. Based on the human-frame admittance control, a stability criterion is derived. By using a human arm stiffness estimator along with the derived stability criterion, a stiffness-based variable admittance controller is designed. The effectiveness of the proposed methods in improving the pHRI performance is tested and supported by simulations and experimental results.